Moderate Genetic Diversity and Genetic Differentiation in the Relict Tree Liquidambar formosana Hance Revealed by Genic Simple Sequence Repeat Markers - Sun, Rongxi; Lin, Furong; Huang, Ping; Zheng, Yongqi (Frontiers in Plant Science, 2016)
Chinese sweetgum (Liquidambar formosana) is a relatively fast-growing ecological pioneer species. It is widely used for multiple purposes. To assess the genetic diversity and genetic differentiation of the species, genic SSR markers were mined from transcriptome data for subsequent analysis of the genetic diversity and population structure of natural populations. A total of 10645 potential genic SSR loci were identified in 80482 unigenes. The average frequency was one SSR per 5.12 kb, and the dinucleotide unit was the most abundant motif. A total of 67 alleles were found, with a mean of 6.091 alleles per locus and a mean polymorphism information content of 0.390. Moreover, the species exhibited a relatively moderate level of genetic diversity (He=0.399), with the highest was found in population XY (He=0.469). At the regional level, the southwestern region displayed the highest genetic diversity (He=0.435) and the largest number of private alleles (n=5), which indicated that the Southwestern region may be the diversity hot spot of L. formosana. The AMOVA results showed that variation within populations (94.02%) was significantly higher than among populations (5.98%), which was in agreement with the coefficient of genetic differentiation (Fst = 0.076). According to the UPGMA analysis and principal coordinate analysis and confirmed by the assignment test, 25 populations could be divided into three groups, and there were different degrees of introgression among populations. No correlation was found between genetic distance and geographic distance (P>0.05). These results provided further evidence that geographic isolation was not the primary factor leading to the moderate genetic differentiation of L. formosana. As most of the genetic diversity of L. formosana exists among individuals within a population, individual plant selection would be an effective way to use natural variation in genetic improvement programs. This would be helpful to not only protect the genetic resources but also attain effective management and exploit genetic resources.